Issues in the handling of cases of tuberculosis in the mortuary. (May 2019) - Stephenson, Lilli; Byard, Roger W.
Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTB) that is most often transmitted by the inhalation of bacteria-containing aerosols. While there has been a decline in numbers of cases in certain countries, large population movements, the increasing emergence of drug-resistant strains and the association with human immunodeficiency virus (HIV) infection make it a disease that is increasingly seen in forensic practice. Mortuary staff are at risk of infection from penetrating sharp injuries, droplet inhalation, ingestion, direct inoculation, through skin breaks or through mucous membranes of the eyes, nose and mouth. While the health and safety measures outlined by agencies may vary slightly, the principles of handling infectious autopsy cases remain the same with awareness and education, immunisation and regular tuberculin testing of staff, pre-necropsy screening of decedents, use of personal protective equipment, and the implementation of safe sharps practices and measures to reduce aerosol formation. Highlights: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Problems are occurring with drug-resistant strains and the association with HIV. Mortuary staff are at risk of infection particularly from penetrating injuries and droplet inhalation. Many agencies provide guidelines for the handling of infectious autopsy cases.